Systematic and Empirical Study of the Dependence of Polyphenol Recovery from Apricot Pomace on Temperature and Solvent Concentration Levels - Dina Cheaib; Nada El Darra; Hiba N. Rajha; Richard G. Maroun; Nicolas Louka (The Scientific World Journal)
This work aims to study the impact of solvent mixture (between 0 and 50% ethanol/water mixture) and temperature (between 25°C and 75°C) levels on the solid-liquid extraction of phenolic compounds (quantity and bioactivity) from apricot pomace. Results show that the mean augmentation of 1% ethanol in the range [0–12%] enhances by three times the extraction of polyphenols compared to the same augmentation in the range [0–50%]. Similarly, the mean augmentation of 1°Celcius in the range [0–25°Celcius] enhances by two times the extraction of polyphenols compared to the same augmentation in the range [0–75°Celcius]. Moreover, 1% of ethanol exhibited a greater impact on the phenolic compound extraction than 1°Celsius. The response surface methodology showed that the optimal extraction condition was reached with 50% ethanol/water at 75°C giving a total phenolic content (TPC) of 9.8 mg GAE/g DM, a flavonoids content (FC) of 8.9 mg CE/g DM, a tannin content (TC) of 4.72 mg/L, and an antiradical activity (AA) of 44%. High-performance liquid chromatography (HPLC) analysis showed that polyphenols were influenced by the selectivity of the solvent as well as the properties of each phenolic compound. Apricot pomace extracts could therefore be used as natural bioactive molecules for many industrial applications.